Advancements and future directions in the sustainable production of epoxy resin-based polymer composites: a comprehensive review - Dag, Mustafa; Aydogmus, Ercan; Arslanoglu, Hasan (Springer Int Publ Ag, 2026)
Epoxy resin-based polymer composites are widely recognized for their outstanding mechanical, thermal, and chemical properties, making them valuable across various high-performance applications. However, challenges in the production process-such as achieving homogeneous filler dispersion, enhancing interfacial adhesion, and optimizing curing parameters-pose significant hurdles. Additionally, the environmental impact associated with composite production has become a critical concern. To address these issues, innovative strategies have emerged, including the integration of advanced fillers, enhancements in curing processes, and the adoption of eco-friendly alternatives. This review synthesizes recent advancements in these areas, highlighting improvements in composite performance and reductions in environmental footprint. While these developments mark significant progress, further research is essential to refine these approaches and establish sustainable production methods that harmonize performance demands with environmental responsibility.
Keywords: Polymer Composites; Epoxy Resin; Environmental Impact; Sustainable Production